Effect of bimetallic (Ca, Mg) substitution on magneto-optical properties of NiFe2O4 nanoparticles. Issue 5 (1st April 2019) - Slimani, Y.; Almessiere, M.A.; Nawaz, M.; Baykal, A.; Akhtar, S.; Ercan, I.; Belenli, I.
Abstract: Nanoparticles (NPs) of calcium and magnesium co-substituted nickel ferrite with the chemical composition Cax Mgx Ni1–2× Fe2 O4 (0.00 ≤ x ≤ 0.05) NPs were prepared hydrothermally. The (Ca, Mg) co-substitution effect on morphological, structural, optical and magnetic properties of NiFe2 O4 NPs was analyzed via FT-IR, XRD, TEM, SEM, DRS and VSM techniques. The magnetization of Cax Mgx Ni1–2× Fe2 O4 (0.00 ≤ x ≤ 0.05) NPs were examined and analyzed at room temperature (300 K; RT) and low temperature (10 K). The specific magnetic parameters such as saturation magnetization Ms, remanence Mr, coercivity Hc, squareness ratio (SQR=Mr /Ms ) and magnetic moment n B of Ni1–2× Mgx Cax Fe2 O4 (0.00 ≤ x ≤ 0.05) NPs were determined and evaluated. The M(H) curves exhibit superparamagnetic behavior at RT and ferrimagnetic nature at 10 K. The substitution significantly changes the magnetizations and coercivity data. An increase in the Ms, Mr, Hc and n B values was observed in substituted products compared to pristine one. The highest values were obtained for x = 0.05 product. The SQR values are found to be below than 0.5, which can be attributed to surface spin disorder effects. The obtained magnetic results are primarily derived from the substitution with Mg and Ca that will strengthen the super exchange interactions.